CORRELATION BETWEEN NUTRITIONAL STATUS AND WAIST CIRCUMFERENCE WITH THE INCIDENCE OF HYPERTENSION IN THE ELDERLY - Munyati Sulam (Universitas Airlangga, 2020)
Background : Hypertension is the main risk factors of cardiovascular diseases that cause mortality. One of the risk factors of hypertension is obesity. Purpose: This study aimed to determine the relationship between nutritional status and waist circumference with the incidence of hypertension in the elderly. Methods: This study was observational analytic with cross-sectional design. The sample in this study was a partial of the elderly who participated in the elderly posyandu as many as 271 respondents. The sampling techniques is simple random sampling. Secondary data in the form of the results of the elderly health checkup at the elderly posyandu in the Sidotopo Wetan Public Health Center (Puskesmas Sidotopo Wetan) in 2018. Results: This study showed that of 271 respondents, there were 107 respondents found with hypertension (39.50%). The majority of hypertension was suffered by respondents with overweight nutritional status (46.70%), and waist circumference with the central obesity category (74.80%). Correlation found between nutritional status and the incidence of hypertension in the elderly (p=0.02<α=0.05; PR=1.32). Prevalence Ratio of 1.32 means that elderly people with overweight nutritional status have the risk of 1.32 times greater to experience hypertension than elderly with underweight and normal nutritional status. No correlation found between waist circumference and the incidence of hypertension (p=0.21). Conclusion: Nutritional status significantly associated with the incidence of hypertension in the elderly. However, waist circumference is not significantly associated with the incidence of hypertension.